Language in mathematics education – On the epistemic and reconstructivistic facet of languaging processes in linguistically heterogenous groups of learners - Kuzu, Taha Ertuğrul (Beta: Jurnal Tadris Matematika, 2023)
[English]: In this article, languaging processes in mathematics education will be reflected from a theoretical and methodological viewpoint. Language is not just a tool for language learning: It is a highly complex medium for transporting meaning. It plays a key role in explaining and fostering as well as reconstructing and interpreting cognitive processes – not only in mathematics education, but due to the abstract nature of mathematical objects in a particularly important way. Thus, language as a mediational dimension is essential in the learners’ as well as researchers’ processes of understanding, be it in interpretational processes or in verbalized, deictical, either explicit or implicit explanations and actions. In this article, this dual-sided perspective will be explained by giving insights into language-related processes of interpreting and understanding mathematical relations in Substantial Learning Environments (SLE’s) as well as relational strategies such as the ‘Auxiliary Task.’ [Bahasa]: Artikel ini membahas proses berbahasa dalam pendidikan matematika dari perspektif teoritis dan metodologi. Bahasa bukan saja sebuah alat untuk pembelajaran bahasa tetapi juga sebuah medium yang sangat kompleks untuk menyampaikan makna. Bahasa memainkan peran penting untuk menjelaskan dan memelihara serta mengembangkan dan memaknai proses kognitif - tidak hanya dalam pendidikan matematika, tetapi karena karakateristik objek matematika yang abstrak sehingga peran bahasa diperlukan. Oleh sebab itu, bahasa sebagai sebuah dimensi mediasional sangat penting dalam proses pemahaman siswa dan peneliti baik itu dalam proses interpretasi atau dalam penjelasan dan tindakan yang diverbalkan, deiktis, baik eksplisit maupun implisit. Dalam artikel ini, perspektif dua sisi ini akan dijelaskan dengan memberikan wawasan ke dalam proses yang berhubungan dengan bahasa untuk menafsirkan dan memahami hubungan matematika dalam konteks Linkungan Belajar Substansial (Substantial Learning Environments, SLE) serta strategi relasional seperti Tugas Tambahan (Auxiliary Task).